Internal dosimetry of [99mTc]NTP15‐5 radiotracer for cartilage imaging in preclinical and clinical models using the GATE Monte Carlo platform. Issue 1 (7th December 2020) - Fois, Giovanna Rosa; Valla, Clémence; Jouberton, Elodie; Sas, Nicolas; Billoux, Tommy; Auzeloux, Philippe; Cachin, Florent; Miot‐Noirault, Elisabeth; Maigne, Lydia
Abstract : Purpose: This study aims to perform dosimetry for [ 99m Tc]NTP15‐5 radiotracer used in imaging of articular cartilage in rabbits and humans. The radiotracer (covered by a world patent WO 01/00621 A1) has been proposed in the previous years for the study of cartilage in osteoarthritis diseases. A sensitive imaging approach is essential to quantify osteoarthritis progression and monitor response to new therapies. [ 99m Tc]NTP15‐5 binds to cartilage proteoglycans whose decreased content is associated to a loss of biomedical function of cartilage. We have implemented the whole dosimetry study concerning this new radiotracer for rabbits and humans using the GATE Monte Carlo platform. Materials and methods: Absorbed doses to critical organs are determined using the MIRD formalism. Biodistribution data are obtained by organ sampling, measuring the activity in organs for three rabbits sacrificed at various times postadministration, and by SPECT/CT imaging at different times after injection. Most important sources are cartilages (in knees and intervertebral discs), due to localization together with the liver and kidneys due to excretion of the agent. S‐values are calculated from rabbit's CT scan and human CT scan using the GATE v8.0 Monte Carlo platform. Cumulated activity in humans is extrapolated from animals using the %kg‐dose/g method. Particular attention is given to dose calculation in bones, bone marrow and organs at risk. Results: The dosimetry performed in rabbits shows highest absorbed doses for liver and kidneys with respectively 22.5 and 43.8 µGy per MBq of injected activity. In humans, we found absorbed doses for a maximum injected activity of 15 MBq/kg, that is, 1050 MBq for an adult of 70 kgs of 9.03 mGy for kidneys and 4.16 mGy for knee cartilages. Effective dose is 2.69 µSv/MBq. Conclusions: The dosimetry profile of [ 99m Tc]NTP15‐5 in the context of preclinical trials is of major importance in order to make sure that organs at risk are not overexposed. GATE provides all the capability needed to calculate dose profiles for internal dosimetry. The extrapolation of the dose for a human model is a first step towards clinical trials.